Chemogenetic modulation of sensory afferents induces locomotor changes and plasticity after spinal cord injury - Eisdorfer, Jaclyn T.; Sobotka-Briner, Hannah; Schramfield, Susan; Moukarzel, George; Chen, Jie; Campion, Thomas J.; Smit, Rupert; Rauscher, Bradley C.; Lemay, Michel A.; Smith, George M.; Spence, Andrew J. (Frontiers in Molecular Neuroscience, 2022)
Neuromodulatory therapies for spinal cord injury (SCI) such as electrical epidural stimulation (EES) are increasingly effective at improving patient outcomes. These improvements are thought to be due, at least in part, to plasticity in neuronal circuits. Precisely which circuits are influenced and which afferent classes are most effective in stimulating change remain important open questions. Genetic tools, such as Designer Receptors Exclusively Activated by Designer Drugs (DREADDs), support targeted and reversible neuromodulation as well as histological characterization of manipulated neurons. We therefore transduced and activated lumbar large diameter peripheral afferents with excitatory (hM3Dq) DREADDs, in a manner analogous to EES, in a rat hemisection model, to begin to trace plasticity and observe concomitant locomotor changes. Chronic DREADDs activation, coupled with thrice weekly treadmill training, was observed to increase afferent fluorescent labeling within motor pools and Clarke’s column when compared to control animals. This plasticity may underlie kinematic differences that we observed across stages of recovery, including an increased and less variable hindquarters height in DREADDs animals, shorter step durations, a more flexed ankle joint early in recovery, a less variable ankle joint angle in swing phase, but a more variable hip joint angle. Withdrawal of DREADDs agonist, clozapine-N-oxide (CNO) left these kinematic differences largely unaffected; suggesting that DREADDs activation is not necessary for them later in recovery. However, we observed an intermittent “buckling” phenomenon in DREADDs animals without CNO activation, that did not occur with CNO re-administration. Future studies could use more refined genetic targeted of specific afferent classes, and utilize muscle recordings to find where afferent modulation is most influential in altering motor output.